Pedagogical practices developed with students with disabilities: a case study at a rural school in Feira de Santana - BA - Priscilia Natália Pereira Ferreira; Klayton Santana Porto (Universidade Federal do Norte do Tocantins, 2020)
This research aims to understand the pedagogical practices developed by the teachers of a school in the countryside of the Municipal Education Network of Feira de Santana-BA, located in the District of Maria Quitéria, in the process of including students with disabilities, enrolled in the final years of the Elementary School. Such investigation was developed through a qualitative descriptive research, carried out through a case study, whose data were collected through semi-structured interviews with two teachers who work with students with disabilities. The results showed that among the main implications of this study, we highlight that, despite the fact that students with disabilities have their enrollment and access to school guaranteed by law, the lack of accessibility and qualified training causes this education provided to them to be neglected. In addition, the investigated teachers pointed out some difficulties for the teaching and learning of students with disabilities, and showed that despite the difficulties faced by the rural school and by them, such as the lack of specialized teaching materials, lack of resources and the lack of interest government agencies, they are concerned with developing differentiated strategies to include them.